The role of L.M. Karakhan in the Chinese policy of the Soviet Union (1923–1926) - I. N. Sotnikova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the 1920s, the young Soviet state pursued several, sometimes mutually exclusive, goals in its policy towards China. On the one hand, the Soviet leadership did its best to achieve international recognition and sought to protect its vital interests. On the other hand, it actively promoted the idea of a world revolution. Under those circumstances, the country’s foreign ministry needed experienced, flexible, and pragmatic diplomats. In this regard, the activities of L.M. Karakhan, who was sent as a Soviet emissary to the Republic of China to address these sensitive issues, are of particular interest. The figure of L.M. Karakhan is all the more remarkable because, being one of the architects of the USSR’s foreign policy towards China, he himself has not received much attention in either Soviet or Russian historiography. On the basis of new archival documents and Chinese primary sources the paper attempts to give a comprehensive assessment of L.M. Karakhan’s tenure first as a plenipotentiary and then as an ambassador of the USSR to China. The first sections consider the tasks of L.M. Karakhan’s diplomatic mission in China and the vicissitudes of the negotiations on the Soviet-Chinese agreement on the establishment of diplomatic relations. To that end, the Soviet diplomat, following the directives from Moscow, flexibly maneuvered between various groupings of Chinese elites and resisted the pressure of other great powers’ representatives. The following sections examine L.M. Karakhan’s activities as a Soviet ambassador. The author concludes that L.M. Karakhan consistently defended the national interests of the USSR, skillfully combining a fine diplomatic game and assertiveness, even rigidity at times. The latter was vividly manifested in the most challenging issues of Soviet-Chinese relations, such as disputes over the status of the Chinese Eastern Railway and Outer Mongolia. At the same time, the ambassador took an active part in organizing and supporting the revolutionary movement in China. In fact, L.M. Karakhan served as a central coordinator of the Soviet aid to the Kuomintang, determining both its forms and substance. The author concludes that L.M. Karakhan proved himself not merely as an agent of the Soviet leadership, but also as a politician in its own right capable to effectively address a wide range of tasks, some of which had not originally been intended by his mission. That said it is worth mentioning that the assertive, tough style of the Soviet diplomat often raised a lot of criticism among foreign representatives, since it was at odds with the declared USSR intentions to break with the foreign policy practices of tsarist Russia.